Assessing Chinese Manufacturing Investments in East Africa: Drivers, Challenges, and Opportunities - Ying Xia (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2019)
In a three-part series comprising two working papers and a briefing paper, Ying Xia dives deep into the investments driving the manufacturing sector as well as agricultural investments in Kenya and Tanzania. The briefing paper offers a honed-in look at the key takeaways while each working paper gives detailed insights into what the industry looks like on the ground. Key takeaways: 1. The author found a considerable disparity between official registration information and on-the-ground investment activities. Neither MOFCOM nor investment authorities in Kenya or Tanzania have been able to monitor small investment projects that are "flying under the radar" or keep track of any subsequent changes to investment plans. 2. Chinese investments in the manufacturing and agricultural industries in Kenya and Tanzania are dominated by private, migrant entrepreneurs, who have mainly been driven by market considerations, such as production cost and market proximity, rather than government incentives in home or host country. 3. Business strategies and decision-making are usually contingent on entrepreneurs' prior experience in China and African countries.
Keywords: 330